Experimental study on the permeability of light transmitting concrete using optical fibers and transparent polymer rods - Ly Quang Huy; Huynh Phuong Nam; Nguyen Minh Hai; Nguyen Duc Tuan; Nguyen Van Huong (Tạp chí Khoa học và Công nghệ)
This study focuses on analyzing the permeability of light transmitting concrete (LTC) using plastic optical fibers (POF) and transparent Polymethyl methacrylate (PMMA) rods with varying diameters and content within the concrete. Experiments were conducted on both thin plate samples to test water penetration time, water absorption and permeability, as well as on cylindrical samples to assess the waterproof grade of the material. Subsequently, a waterproofing layer using a Siloxane-based material layer was applied to the concrete samples. The experimental results shown that using small-diameter optical fibers results in lower permeability compared to using large-diameter PMMA rods. This is because the bond between the optical fibers and the concrete is better than that when using PMMA rods. Additionally, increasing the content of PMMA rods significantly increased the water permeability of the material.